Nanoreactors for nanostructured materials - Khomane, Ramdas B.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2008)
Organized systems such as micelles, reverse micelles, vesicles, polyelectrolyte capsules, liquid crystals, etc., formed through a self-assembling process represent nanoreactors that can be used for preparing nanostructured materials. Besides a fascinating academic subject, these nanoreactors provide a unique way to develop a special type of advanced material for a wide variety of applications in electronics, photonics, biomedical and other areas. The article examines the formation, functioning, properties and special attributes of these nanoreactors with a view towards their engineering analysis, design and possible integration in manufacturing technology.
Keywords: nanoreactors; Nanostructured materials; organized self-assemblies